Relación entre los determinantes sanitarios y ambientales de la salud con el riesgo urbano en desastre, Municipio de Sabaneta, 2016 - Gil Martínez, Adriana Patricia
Sabaneta has a degree of urbanization of 79.63% according to the report of the analysis of the health situation (Castrillón, 2013), indicating that there is a high concentration of people in urban areas, taking shape a possible increased vulnerability to disasters, in relation to the environmental determinants of health such as: the impact of urban planning, housing conditions, water management and land use. This research seeks to understand the relationship between environmental health determinants of health, with urban disaster risk from the perspective of the community in 2016 in Sabaneta. This is done under a qualitative approach with a hermeneutical methodology under a grounded theory research design, seeking to identify cultural factors, perception of the phenomenon subjects living conditions and lifestyles of them. The collection of information is done through semi-structured interviews with key informants. Following transcription, hoping to find information that will allow analysis categories, as already suggested, establish the relationships between environmental health determinants of health, with urban disaster risk in order to conclude the level of involvement will be analyzed. In addition results are expected to contribute as input for the authorities and community can generate actions for prevention, mitigation and response.